Effect of ethnicity on performance in a final objective structured clinical examination: qualitative and quantitative study. Issue 7393 (12th April 2003) - Wass, Val; Roberts, Celia; Hoogenboom, Ron; Jones, Roger; Vleuten, Cees Van der
Abstract: Objective: To assess the effect of ethnicity on student performance in stations assessing communication skills within an objective structured clinical examination. Design: Quantitative and qualitative study. Setting: A final UK clinical examination consisting of a two day objective structured clinical examination with 22 stations. Participants: 82 students from ethnic minorities and 97 white students. Main outcome measures: Mean scores for stations (quantitative) and observations made using discourse analysis on selected communication stations (qualitative). Results: Mean performance of students from ethnic minorities was significantly lower than that of white students for stations assessing communication skills on days 1 (67.0% (SD 6.8%) and 72.3% (7.6%); P=0.001) and 2 (65.2% (6.6%) and 69.5% (6.3%); P=0.003). No examples of overt discrimination were found in 309 video recordings. Transcriptions showed subtle differences in communication styles in some students from ethnic minorities who performed poorly. Examiners' assumptions about what is good communication may have contributed to differences in grading. Conclusions: There was no evidence of explicit discrimination between students from ethnic minorities and white students in the objective structured clinical examination. A small group of male students from ethnic minorities used particularly poorly rated communicative styles, and some subtle problems in assessing communication skills may have introduced bias. Tests need to reflect issues of diversity to ensure that students from ethnic minorities are not disadvantaged.